Marger Kolongmerat sebagai Strategi Peningkatan Market Power Melalui Diferensiasi : Penelitian - Khairani Alawiyah Matondang; Ainun Saskia; Khairunnisa Br Marpaung; Ledi Marina Purba; Kevin Daniel Sirait (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to examine how conglomerate mergers can be used as a strategy to strengthen market power through the implementation of product differentiation. Using a qualitative approach and case study method on several national and international companies such as the Disney-Fox merger and Indosat Ooredoo Tri, this study focuses on understanding post-merger product differentiation strategies in strengthening the company's competitive position in the market. The analysis results show that conglomerate mergers have two main functions: first, as an instrument for market expansion and increasing company value through innovation, bundling strategies, and strengthening brand image; second, as a means to create barriers to entry and increase switching costs for consumers. The Disney-Fox case study emphasizes the importance of intellectual property ownership and exclusive content as strategic advantages in maintaining customer loyalty. Meanwhile, the Indosat Tri merger emphasizes infrastructure integration and digital service development as a form of service-based differentiation. Although conglomerate mergers can increase efficiency and strengthen a company's competitive position, potential risks such as increased market concentration and reduced consumer choice still need to be monitored. Therefore, the role of supervisory institutions such as the KPPU is crucial in ensuring that the implementation of mergers remains in accordance with the principles of fair competition and maintains a balance between the interests of business actors and consumer protection.